Primary lung carcinoma in children and adolescents – Clinical characteristics and outcome of 12 cases from the German registry for rare paediatric tumours (STEP). (October 2021) - Voggel, Sarah; Abele, Michael; Seitz, Christian; Agaimy, Abbas; Vokuhl, Christian; Dirksen, Uta; Bier, Andrea; Flaadt, Tim; Classen, Carl F.; Claviez, Alexander; Schneider, Dominik T.; Brecht, Ines B.
Highlights: Presenting symptoms are unspecific and etiology differs from adult lung carcinoma. Children diagnosed with mucoepidermoid carcinoma face a favourable outcome. Adenocarcinoma and squamous cell carcinoma are prognostically unfavourable entities. Survivalmight be improved by molecular profiling and targeted therapies. International collaboration is essential for distinct paediatric therapy protocols. Abstract: Objectives: Primary lung carcinomas are very rare paediatric tumours with an incidence of < 2/1.000.000 per year. They are clinically and histologically heterogeneous, and there are no therapeutic guidelines for this age group. Therefore, they represent a challenge for treating physicians. This analysis was performed to expand knowledge on characteristics, treatment and prognosis of primary lung carcinoma in paediatric patients. Material and methods: Between 2009 and 2019, twelve children and adolescents with lung carcinoma were identified in the prospective German registry for rare paediatric tumours (STEP). Data were analysed for histopathological entities, symptoms, diagnostics, therapy, clinical course and outcome. Results: Mucoepidermoid carcinoma (MEC) was the most frequent entity (n = 7), followed by adenocarcinoma (n = 2), squamous cell carcinoma (SCC; n = 2) and adenosquamous carcinoma (n = 1). Patients presented with non-specific symptoms and often, they were initially mistreated for airway infections. Patients with MEC showed no metastases and were successfully treated with complete resection. Patients with adenocarcinoma and SCC were older than 16 years of age at diagnosis. While patients with SCC presented with distant metastases and died within one year after diagnosis, those with adenocarcinoma and adenosquamous carcinoma achieved complete remission after multimodal treatment. Conclusions: Presenting symptoms of lung carcinomas are unspecific and therefore, diagnostic evaluation and treatment are difficult. In the absence of carcinogen exposure, etiology seems to differ from adult lung carcinoma. Children diagnosed with MEC face a favourable outcome. In contrast, patients with prognostically unfavourable adenocarcinoma and SCC might benefit from molecular profiling and targeted therapies. International collaboration for the establishment of treatment protocols adjusted for distinct features of primary lung carcinoma in childhood is essential.